2021
DOI: 10.1101/2021.05.29.21258041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting COVID-19 Number of Cases by Implementing ARIMA and SARIMA with Grid Search in United States

Abstract: COVID-19 has surged in the United States since January 2020. Since then, social distancing and lockdown have helped many people to avoid infectious diseases. However, this did not help the upswing of the number of cases after the lockdown was finished. Modeling the infectious disease can help the health care providers and governors to plan ahead for obtain the needed resources. In this manner, precise short-term determining of the number of cases can be imperative to the healthcare system. Many models have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In this paper, ARIMA and SARIMA were selected for prediction, and the optimal model parameters for each were found using a grid search. According to the findings, ARIMA performs better than SARIMA in predicting, whereas the Holt-Winters Double Exponential model surpasses the Exponentially Weighted Moving Average and Simple Moving Average [4]. This paper aimed to assess how well the ARIMA model predicted the spread of COVID-19, which the World Health Organization designated a global pandemic in March 2020 after infecting over 4 million people and killing over 300,000 by early May 2020.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, ARIMA and SARIMA were selected for prediction, and the optimal model parameters for each were found using a grid search. According to the findings, ARIMA performs better than SARIMA in predicting, whereas the Holt-Winters Double Exponential model surpasses the Exponentially Weighted Moving Average and Simple Moving Average [4]. This paper aimed to assess how well the ARIMA model predicted the spread of COVID-19, which the World Health Organization designated a global pandemic in March 2020 after infecting over 4 million people and killing over 300,000 by early May 2020.…”
Section: Related Workmentioning
confidence: 99%
“…In such a way, the pandemic could be monitored, controlled, and properly managed. Many studies demonstrated that among the epidemiological models, the ARIMA model showed the desired precision in predicting the number of cases and fatalities with minimum error[ 10 , 18 ].…”
Section: Time Series Analysis For Assessment Of Spread Of Sars-cov-2 ...mentioning
confidence: 99%
“…Many other research groups confirmed the effectiveness and usefulness of the ARIMA model for COVID-19 pandemic forecasting[ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 97%
“… This study reported that NNAR model as the best model for forecasting COVID-19 in Turkey. Saina et al [31] 3 2 3 (3,2) (2,0) (3,2) NA NA NA Holt-Winter Exponential smoothing additive (HWESA) model. They reported that HWESA model outperformed ARIMA and SARIMA models.…”
Section: Introductionmentioning
confidence: 99%